Exploring the Developmental Potential of Human Germinal Vesicle Oocytes Aiming at Fertility Preservation: Can We Increase the Yields of Competent Oocytes through IVM Combined with Vitrification? - Hao, Xia; Phoon, Jessie; Barbunopulos, Lina; Sheikhi, Mona; Reyes Palomares, Arturo; Rodriguez-Wallberg, Kenny (MDPI, 2022)
The rescue in vitro maturation (rIVM) of germinal vesicle oocytes (GVs) has been proposed to improve the total number of mature oocytes in women undergoing fertility preservation. Currently, there is no consensus about the clinical utility of this practice, and heterogeneity in the protocols used may influence the final outcomes. This study investigated the developmental potential of mature metaphase II (MII) human oocytes obtained from GVs after rIVM and the impact of applying vitrification at different timepoints either before or after rIVM. After randomization, oocytes were assigned to undergo rIVM and thereafter vitrification or intracytoplasmic sperm injection (ICSI), or to undergo direct vitrification-warming and thereafter rIVM and ICSI. The likelihood of obtaining MII oocytes was just slightly higher in the fresh rIVM group compared to the vitrification-warming-rIVM group. When comparing fresh rIVM that underwent subsequently ICSI, the fertilization and developmental rates up to the blastocyst stage were seen to be reduced in both groups that underwent vitrification either before or after rIVM. Although some blastocysts were obtained in the fresh rIVM-ICSI group, the efficacy of these methods was low overall, suggesting that the further development of protocols for IVM conducted early after denudation is needed to improve the final results of rIVM aiming at fertility preservation.
Keywords: Reproducción humana asistida; Fecundación in vitro; Fertility preservation; Immature oocyte; Germinal vesicle; Vitrification; In vitro maturation; Fertilization; Blastocyst